Outcomes of Kawasaki Disease Children With Spontaneous Defervescence Within 10 Days - Ya-Chiao Hu; Hsin-Min Liu; Ming-Tai Lin; Chun-An Chen; Shuenn-Nan Chiu; Chun-Wei Lu; Luan-Yin Chang; Jou-Kou Wang; Mei-Hwan Wu (Frontiers Media S.A., 2019)
Background: Kawasaki disease (KD) is one of the most common vasculitis in childhood. Intravenous γ-immunoglobulin (IVIG) is recommended to be administrated within 10 days after fever onset. However, some patients didn't have IVIG therapies because of atypical disease presentations or spontaneous defervescence. We aimed to evaluate the coronary outcomes of the KD patients who didn't receive IVIG and had defervescence within 10 days.Methods: We retrospectively reviewed the KD patients in NTUCH between 2008 and 2015. The patients with a diagnosis of KD and had a febrile length between 5 and 10 days were enrolled. Days of fever, clinical symptoms, laboratory data at the acute stage, and series of coronary artery measurements within a minimum of 3 months after disease onset were recorded. Risk factors associated with coronary lesions 1 month after KD onset were also analyzed.Results: Two hundred ninety-three eligible KD patients were enrolled (Male: 55.1%, mean age of onset: 1.8 years old). Thirty-seven patients had spontaneous defervescence without IVIG treatment. The incidence of coronary aneurysms at the 4th week after disease onset was higher in spontaneously defervesced KD patients than those treated with IVIG (18.9% vs. 5.1%, p = 0.002). Interestingly, of the 238 KD patients without coronary lesions at their acute phase, percentages of emerging coronary aneurysms became significantly higher if they didn't have IVIG therapies due to spontaneous defervescence (4/31), compared with those who received IVIG (3/208). Further analysis showed the development of coronary lesions at 1 month after disease onset was associated with younger age (<12 months old, p = 0.024), and leukocytosis (WBC > 17,000/cumm, p = 0.031).Conclusions: 18.9% of KD patients with spontaneous defervescence had coronary aneurysms. Even without initial coronary lesions, such patients were still riskier to develop coronary aneurysms, compared with KD patients who received IVIG therapies. Such findings address the importance of refining the strategy for use of IVIG in the spontaneously defervesced KD patients within 10 days after fever onset, at least in those with age younger than 1 year and those with leukocytosis.